Pengaruh PMA, PMDN, dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Auliya Ramadani; Puti Andiny; Yani Rizal; Safuridar Safuridar (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study aims to analyze the effect of Foreign Direct Investment (FDI), DomesticDirect Investment (DDI) and Government Expenditure on economic growth in Aceh Province. In this analysis using multiple linear regression analysis models using eviews 10 software. The data used is secondary data (time series) taken from 2009-2023 for 15 years sourced from BPS (Central Bureau of Statistics) Aceh Province. The results of this study indicate that Foreign Direct Investment (FDI) has a probability value of 0.0595> 0.05, it can be concluded that FDI has no significant effect on economic growth in Aceh Province. Domestic Investment (PMDN) has a probability value of 0.9494> 0.05, it can be concluded that PMDN has no significant effect on economic growth in Aceh Province. Government spending has a probability value of 0.6689> 0.05, it can be concluded that government spending has no effect on economic growth in Aceh Province.